A atuação do professor-psicopedagogo na escola : suas implicações no processo de escolarização - Pöttker, Caroline Andrea (2012)
In schools has significantly increased the number of students with problems in the schooling process, leading teachers, educational counselors, coordinators and principals to forward these, professionals such as psychologists, phonoaudiologist, neurologists, psychiatrists and others. Another professional who has been asked frequently to serve this audience is psychopedagogists. This professional, who have studied for a specialization in educational psychology, is now calling himself a psychopedagogists and act in clinics and in school as if it were a qualified professional with knowledge of two major areas - Psychology and Pedagogy - thus exerting activities that involve these two concomitantly areas. And in our professional practice, we detect who actually are in the clinical and educational psychologists, particularly in schools, working mainly with children with problems at school. This finding prompted us to study on this issue, and for that, we involve some public schools in a city in the western regions, where there are professionals occupying a position called teacherpsychopedagogists. This study therefore aimed to investigate who is this professional by identifying how their performance in school and their implications in teaching-learning process, and understand why it was necessary to present this work in schools and this is taking spaces of other professionals such as psychologist and educator. It constitutes an empirical research and literature that sought to articulate the history of Psychology, Educational Psychology and Pedagogy identifying their interconnections and understanding the role of professionals in these areas. This work was guided by the Historical-Cultural Psychology, which has Vygotsky, Luria and Leontiev as its main representatives. Empirical research with the participation of ten teachers educational psychologists working in five public schools of that city. Data collection was conducted through semi-structured interview technique, based on a script consisting of five items. To analyze the data collected was used to analyze the content and structure of categories. The results showed that the position of professor-psychopedagogists was occupied by teachers who have worked in the capacity of teacher in school and have the title of specialist Psychopedagogy were removed from it to assume its position. According to most of these professionals, your role is to assist the teacher in that classroom has students with learning difficulties and try to understand why these students are not learning, and especially help them in reversing this problem. Thus, the main activities developed by them are: pedagogical assessment, referrals to specialized professionals, guidance and support to teachers, group care to students, and assistance to parents. The results also allow us to see that the activities undertaken by teachers, educational psychologists are similar to those of psychologists and pedagogues. However, what differentiates the activities performed is subsidized by the instrumentalization theoretical foundation that guides practitioners in their interventions. Thus, participants revealed act based on two competing theories, the Historical-Cultural Psychology and Constructivism. Moreover, one can observe that the teacher understands psychopedagogists-teaching-learning process as the assumptions of Constructivism. We therefore conclude that the performance of this professional in these schools, the explanations for the academic difficulties are centered on the individual and not in the teaching-learning process.